An unknown source concerning Esaias Reusner Junior from the Music Collection Department of Wroclaw University Library - Joachimiak, Grzegorz (Interdisciplinary Studies in Musicology, 2018)
The Music Collection Department of Wroclaw University Library is in possession of an old print that contains the following inscription: ‘Esaias Reusner | furste Brigischer | Lautenist’. This explicitly indicates the lutenist Esaias Reusner junior (1636-1679), who was born in Lwówek Śląski (Ger. Lówenberg). A comparative analysis of the duct of the handwriting in this inscription and in signatures on letters from 1667 and 1668 shows some convergences between the main elements of the script. However, there are also elements that could exclude the possibility that all the autographs were made by the same person. Consequently, it cannot be confirmed or unequivocally refuted that the inscription is an autograph signature of the lutenist to the court in Brzeg (Ger. Brieg). The old print itself contains a great deal of interesting information, which, in the context of Silesian musical culture of the second half of the seventeenth century and biographical information relating to the lutenist, enable us to become better acquainted with the specific character of this region, including the functioning of music in general, and lute music in particular. The print contains a work by Johann Kessel, a composer and organist from Oleśnica (Ger. Ols), who dedicated it to three brothers of the Piast dynasty: Georg III of Brzeg, Ludwig IV of Legnica and Christian of Legnica. It is a ‘Paean to brotherly unity”, which explains the reference to Psalm 133. Published in Brzeg, for the New Year of 1663, by Christoff Tschorn, the print also includes two poetic texts: a sophisticated elegiac distich in the form of a tautogram and a New Year’s ode. It is beneath these texts that we find the above-mentioned inscription relating to Esaias Reusner Jnr. Regardless of whether the autograph on the print is ascribed to Reusner or not, it does indicate his connection with this print, and probably with Kessel’s composition as well. Consequently, we can discover what kind of repertoire the Silesian lutenist played besides familiar lute pieces by his teachers, his own works, and arrangements of his works for chamber ensemble.